Paliperidone Palmitate Once-Monthly Injectable Treatment for Acute Exacerbations of Schizoaffective Disorder. Issue 4 (August 2016) - Fu, Dong-Jing; Turkoz, Ibrahim; Simonson, R. Bruce; Walling, David; Schooler, Nina; Lindenmayer, Jean-Pierre; Canuso, Carla; Alphs, Larry
Abstract : Abstract: The optimal treatment for schizoaffective disorder (SCA) is not well established. In this initial 6-month open-label treatment period of a large, multiphase, relapse-prevention study, the efficacy and safety of paliperidone palmitate once-monthly (PP1M) injectable were evaluated in subjects with symptomatic SCA. Subjects with acute exacerbation of SCA (ie, with psychotic and either depressive and/or manic symptoms) were enrolled and treated with PP1M either as monotherapy or in combination with antidepressants or mood stabilizers (combination therapy group). After flexible-dose treatment with PP1M for 13 weeks, stabilized subjects continued into a 12-week fixed-dose PP1M treatment period. A total of 667 subjects were enrolled; 320 received monotherapy and 347 received PP1M as combination therapy; 334 subjects completed the entire 25-week treatment. Statistically significant and clinically meaningful improvements from baseline were observed for all efficacy measures in psychosis (per Positive and Negative Syndrome Scale), mood symptoms (per Young Mania Rating Scale and Hamilton Depression Rating Scale—21 items), and functioning (per Personal and Social Performance Scale) from week 1 to all time points during the 25-week treatment period ( P < 0.001). Similar improvements in efficacy measures were observed between subjects receiving monotherapy or combination therapy. Efficacy benefits persisted throughout the 25-week period. The most common adverse events were akathisia (11.1%), injection-site pain (10.6%), and insomnia (10.0%). Paliperidone palmitate once-monthly administered as monotherapy or in combination with mood stabilizers or antidepressants in patients with an acute exacerbation of SCA provided rapid, broad, and persistent reduction in psychotic, depressive, and manic symptoms, as well as improved functioning. Abstract : Supplemental digital contents are available in the text.